Traffic State Detection Based on Multidimensional Data Fusion System of Internet of Things. (2nd July 2021) - Zhang, Jinxi; Zhu, Wenying; Wu, Xueying; Ma, Tianshan
Abstract : In recent years, the rapid development of cloud computing, mobile Internet, Internet of Things, and other technologies has accelerated the explosive growth of the number and types of data in various industries. As one of the current hot research fields, the multidimensional data fusion system has received widespread attention all over the world. Road traffic and traffic management involve a wide range of participants; a variety of traffic behavior and traffic management means have produced a huge volume of traffic management data and have a very high application value. Therefore, it is of great significance to study the application mode of the traffic management multidimensional data fusion system and realize the asset value transformation of the multidimensional data fusion system. Starting from the safety supervision service of operating vehicles, this paper elaborates the traffic management multidimensional data fusion system platform for the safety supervision service of operating vehicles around the application requirements and architecture of the traffic management multidimensional data fusion system and the results of this research team. Paper with city comprehensive transport hub as the research object uses the Internet of Things technology; establishes a set of BIM model-based intelligent Internet operation management platform, multidimensional collection personnel, and vehicles, such as traffic, equipment, and business data information; realizes the integration of data, correlation, and instructions issued by ability, to support the building intelligence operation management needs of the business; and realizes traffic and transportation status detection.